Odds and Ends - Heyn, Maura; Raja, Rubina (Brepols, 2023)
The funerary art that was produced in Roman Palmyra, a caravan city in the Syrian steppe desert, is rightly world-renowned. The frontal depictions of the deceased, featured in torso-length portraits, and the large-scale banqueting scenes are iconic, and lent an added mystique by the absence of any literary sources that might aid in their interpretation. But while from a distance these exquisite portraits might seem rather formulaic, when examining more closely, it is clear that these scenes reveal a surprisingly rich and varied funerary décor. Alongside the more popular iconographic choices are singular scenes, motifs, and elements that deviate from the norm, while new patterns and connections between Palmyra and its surroundings are identifiable. This volume, which draws on the vast materials gathered under the auspices of the Palmyra Portrait Project directed by Professor Rubina Raja, explores the ‘oddities’ raised by the Palmyrene corpus; it examines one-off scenes or elements, and unusual or unparalleled iconographical choices, and questions how and why such unusual choices should be interpreted. The chapters gathered here not only focus on these visual ‘hapax legomena’ in Palmyra, but also explore the city’s connections with the art of Roman centres to the west, as well as the nearby Hellenistic city states, regional centres of production, and Parthian and Persian sites to the east. Through this approach, the authors engage with the visual richness and sheer amount of choice that existed in Palmyrene funerary art, while also providing unique insights into the knowledge culture that existed within Palmyrene society.